Influence of Atmospheric Air Quality on the Morbidity of the Population Living in the Region of Oil and Gas Production in the Republic of Kazakhstan - AITMAGANBET, Perizat; UMAROVA, Gulmira; SABYRAKHMETOVA, Valentina; PEREPELKIN, Sergey; DOSKABULOVA, Dariya; URGUSHBAEVA, Gulnur; EGIZBAEVA, Dina (Journal of Environmental Management and Tourism, 2020)
Sarkuland Kenkiyak settlements are located in the Aktobe province, at18-20 km from the oil and gas producing field "Zhanazhol", in the northwest region of the Republic of Kazakhstan. To evaluate the exposure of the adult male and female population living in Sarkul and Kenkiyak settlements, a single medical study was conducted. The nonparametric method of the Spearman correlation analysis was performed between the mean concentration of substances exceeding the Maximum Permissible Concentration and the classes of newly diagnosed diseases. Selection and analysis of air samples was carried out according to the developed research protocol; the qualitative-quantitative analysis was carried out on the Gas analyzer HANK-4 apparatus. Significant pollution of atmospheric air by carbon monoxide, benzapyrene, dust and phenol were identified in places. Correlation dependencies between these pollutants of air and the diseases of the population revealed as a result of medical examination are established, as a result of diseases of the circulatory system, ear and mastoid process, nervous system and digestive organs; between the concentration of carbon monoxide and diseases of the circulatory system, the digestive system, the genitourinary system and the musculoskeletal system; between nitric oxide and diseases of the digestive system and the circulatory system; between benzopyrene and diseases of the digestive system, the genitourinary system and the nervous system.